Filme Lutero - Aguilar, Rúben (Kerygma, 2006)
Luther. Alemanha, 2003; Drama - 112 min; Direção: Eric Till. Roteiro: Camille Thomasson, Bart Gavigan. Elenco: Joseph Fiennes, Alfred Molina, Bruno Ganz, Jonathan Firth, Peter Ustinov, Claire Cox, Uwe Ochsenknecht, Benjamin Sadler; Estúdio: NFP teleart / Eikon Film / Thrivent Financial for Lutherans; Distribuição: UIP / Pandora Filmes